Effectiveness of the Talaqqi Method in Children's Scripture Memorization within the SDGs Framework: A Case Study in Indonesian Elementary Schools - Suwardi; Endang Fauziyati; Syamsul Hidayat (Universitas Muhammadiyah Surakarta, 2024)
Objective: This study aims to describe the methods of memorizing the Holy Scripture, identify similarities and differences in implementation, and assess the effectiveness of these methods in elementary school settings. Grounded in a case study design, the research was conducted in three Indonesian elementary schools that actively implement Holy Scripture memorization programs. Theoretical framework: The theoretical framework guiding this study integrates behavioral and humanistic learning theories, which emphasize structured repetition, teacher modeling, and personalized emotional engagement. Literature review: The literature on Quranic memorization highlights the importance of oral transmission and teacher-student interaction, particularly through the talaqqi method. However, few studies have provided a comparative analysis across different schools using this method within the broader context of child education and the Sustainable Development Goals (SDGs). Methods: Data were collected from teachers, students, and parents through interviews, observations, and document analysis. The data were then processed using the descriptive-interpretative model proposed by Miles, Huberman, and Saldana, involving data reduction, display, and conclusion drawing. Results: The findings reveal three main outcomes: (1) all schools apply two core memorization methods—talaqqi wal mushahabati and talaqqi wal istiqlali—each utilizing three tone techniques: free tone, UMMI two-tone rost, and AN-NUR four-tone rost; (2) all schools shared a common approach grounded in behaviorist-humanist integration; and (3) differences were observed in tone applications, which influence students’ engagement and retention. Implications: The implication of this study suggests that the talaqqi method is highly effective for elementary-level students, as it aligns with their psychological development and supports consistent memorization outcomes. Novelty: The novelty of this research lies in its integration of traditional Islamic pedagogy—specifically the talaqqi method—with the Sustainable Development Goals (SDGs), offering a unique framework for promoting inclusive, equitable, and quality religious education for children in elementary schools within a modern global development context.